L’impact De La Formation, Selon Les Normes Qualite, Sur L’implication Du Personnel Sous Contrats Flexibles : Resultats D’une Etude Empirique - Mbarki, M. Mohamed Amine; Rharzouz, M. Jaouad; Boubker, M. Omar (European Scientific Journal, ESJ, 2018)
This paper introduces the raising interests of certified automotive companies of Tangier-Tétouan region on quantitative flexibilization strategies, via atypical contracts. Therefore, the involvement paradox remains significant through contracts’ flexibility. Thus, the present study aims to analyze the training practices impact according to quality standards on stuff involvement under integration contract. On the methodological standpoint, we have combined between an exploratory qualitative approach and a confirmatory quantitative approach, on the basis of a sample of 170 operators under integration contracts in Moroccan automotive industry. The results show that employees ‘training influences positively on their level of emotional involvement.